Penerapan Model Pembelajaran Koopeartif Tipe Cooperative, Integrated, Reading and Composition (CIRC) Pada Materi Struktur Atom dan Sistem Periodik Unsur Kelas X SMAN 1 Pasangkayu - Yuliana, Dewi; Walanda, Daud K.; Ratman, Ratman (Universitas Tadulako, 2014)
Reaserch was conducted on the atomic structure subject and the periodic table with implementing cooperative learning model type of coopeative, integrated reading and composition (CIRC) in SMAN 1 Pasangkayu is applied to the learning model with the conventional lecture method. This study aims to implement cooperative learning model of CIRC towards the chemical learning outcomes. The population in this study is a class X student of SMAN 1 Pasangkayu academic year 2013/2014 the number of students 300 people, and the study sample X.4 class as experiment class with (n = 30) applying cooperative learning model CIRC and class X.3 as class control the number of students (n = 32) whithout using cooperative learning model CIRC. Testing the hypothesis t-test of the right-hand side. The results of the analysis of data obtained average scores on the experimental class = 76.90 and 60.81 for the control class normaly distibuted both classes and has variance (F test) are homogeneous. Tesing hypothesis obtained tcount t-test = 4.73 > ttabel = 1.67 with a significance level (Î±) = 0.05. The results showed that the application of cooperative learning model CIRC gives the positive effect on student learning outcomes in the atomic structure subject and the periodic table of elements (H0 rejected H1 is accepted).